Instructions to Rate Genital Vasocongestion Increases Genital and Self‐Reported Sexual Arousal but not Coherence Between Genital and Self‐Reported Sexual Arousal. (10th July 2013) - Prause, Nicole; Barela, James; Roberts, Verena; Graham, Cynthia
Abstract: Introduction: Women are often reported to have a low coherence (often referred to as "discordance" in sexuality literature) between their genital response and self‐reported sexual arousal. Aim: The purpose of this study was to determine whether differing instructions for rating sexual arousal would increase the coherence between genital response and self‐reported arousal in women. Methods: Genital responses were recorded, using vaginal photoplethysmography, from 32 young women while they fantasized in three different conditions. Conditions instructed women to rate their overall sexual arousal, any physical cues, and genital blood flow. Main Outcome Measures: The primary outcome measure was the coherence of vaginal pulse amplitude (VPA) and reported sexual response in the three conditions. Results: Unexpectedly, both VPA response and self‐reported sexual arousal were higher when women were asked to rate their genital blood flow. Examining only participants who reported at least some sexual arousal in all conditions (n = 17), coherence was highest when women were instructed to rate overall sexual arousal. Conclusion: Results suggest that focusing on genital blood flow during sexual fantasy may increase women's (self‐reported and genital) sexual response. Focusing on any physical arousal cues during sexual fantasy was associated with lower coherence of women's genital response and self‐reported arousal compared with when they were instructed to rate their overall sexual arousal.Prause N, Barela J, Roberts V, and Graham C. Instructions to rate genital vasocongestion increases genital and self‐reported sexual arousal but not coherence between genital and self‐reported sexual arousal. J Sex Med 2013;10:2219–2231.